PENGARUH EPS, PER, KEBIJAKAN DIVIDEN, FIRM SIZE (SIZE), DAN BOOK VALUE (BV) TERHADAP HARGA SAHAM PERUSAHAAN PADA INDEKS LQ45 TAHUN 2009-2012 - Suherman .; Estu Setiyoaji; Gatot Nazir Ahmad (Jurnal Manajemen., 2015)
The purpose of this study is to know the effect of Earning Per Share (EPS), Price Earning Ratio (PER), Dividend Policy, Firms Size (SIZE), and Book Value (BV) on stock price with partially and simultaneously. Dividend policy is measured by Dividend Per Share (DPS). And firm size is measured by sales company. The research model in this study used panel data analysis. The samples are 51 firms listed on Index LQ-45 in 2007- 2010 selected by purposive sampling method. The empirical results partially show that Earning Per Share (EPS), Price Earning Ratio (PER), and Book Value (BV) have positive significant effect on stock price. Further, dividend policy and firm size do not have positive significant effect on stock price. Beside that the result simultaneously showed that Earning Per Share (EPS), Price Earning Ratio (PER), Dividend Policy, Firms Size (SIZE), and Book Value (BV) have significant effect on stock price.